Recommendations for postpartum athletes returning to sport: the past, present, and future - Irani, C. R.; Turner, E. H. G.; Rumps, M. V.; Mulcahey, M. K. (The Physician and Sportsmedicine, 2024)
Introduction There is a growing percentage of elite female athletes who choose to start a family during their athletic careers. Current guidelines to manage postpartum elite athletes returning to sport are weakly rooted in athlete-centered evidence and/or are restricted by small sample sizes. The purpose of this review was to collect and compare existing protocols and guidelines for elite athletes returning to sport following childbirth and to highlight the current culture surrounding postpartum athletes.